Modeling of xylitol production based on xylose fermentation by Candida tropicalis - Mohamad, Nurul Lina (2018)
Xylitol is a five carbon sugar alcohol and identified as one of the top ten chemicals derived from carbohydrates. It can be produced from bioconversion of xylose through fermentation. This study aims to develop a model and predict the xylitol production using a yeast, Candida tropicalis. The fermentation conditions of xylitol production were obtained by varying agitation speed (300 to 600 rpm), initial xylose concentration (50 to 250 g/L), pH (3 to 6.5) and temperature (25 to 40°C) using 5 L bioreactor. Kinetic parameters such as yield and productivity were calculated in a xylose batch fermentations in order to construct the model. The growth of C. tropicalis was expressed by a modified Monod model that incorporates limitation and inhibition in the fermentation medium. The experimental data from a series of batch fermentation with different fermentation conditions were used to estimate the unknown parameters and simulated by gPROMS software. Ten unknown parameters (A, δ, KO2, Keq, Kin,S, Kin,P, Kin,O2, Kδ, Kli,P, YO2) were estimated by simulation to obtain a best fit to the data with 95% significant of the model. The influence of pH and temperature on cell activities was further investigated and quantified. Eight more kinetic parameters (μmax,S0, kμ1, kμ2, Topt, nT, σ0, EC, σ) that are included in the new model based on the pH and temperature to the cell growth rate were then established. The non-linear equation system comprising twenty one equations were construct to model the behavior of xylose fermentation. The values of xylitol yield (YPS), cell yield (YXS) and maximum specific growth rate (μmax) were fitted and were obtained with average values of 0.36 g xylitol/g xylose, 0.12 gcell/gxylose and 0.12 h-1, respectively. The results obtained from the simulations suggest that the proposed model fits accurately the experimental data. The accuracy of the model were then validated in the 50 L bioreactor. The highest xylitol and cell yield was estimated of 0.71 gxylitol / gxylose and 0.48 gcell / gxylose at temperature 32°C, pH 5, agitation speed of 400 rpm and 50 g/L of xylose concentration.